Talking About the Past that Lingers in Our Present - Olga M. Mladenova (Slavia Meridionalis, 2025)
This article reviews theory-guided research at the intersection of Germanic and Slavic studies that integrates quantitative and qualitative analysis. Showcasing a mutually beneficial symbiotic relationship between theory and empirical inquiry, the book details valuable insights that a theory-trained eye can glean from scant data scattered in diverse texts that are written in various languages at different points in time, and demonstrates how such findings in turn finetune the theory.